Effect of tetracycline on microbial community structure associated with enhanced biological N&P removal in sequencing batch reactor - Liu, Hang (2020)
The presence of antibiotics in wastewater has raised serious concerns about its potential impacts on biological nitrogen and phosphorus (N&P) removal. This study investigated the long-term process performance and microbial structures in response to tetracycline in the enhanced N&P removal process. Results showed that trace tetracycline (20 and 50 μg/L) had no obvious effect on the N&P removal, while the relative abundances of Nitrospira and poly-phosphate accumulating organisms (PAOs) were found to increase. Moreover, the decreased abundance of ammonia oxidizing bacteria (AOB) was observed. When the tetracycline concentrations were further increased to 2 and 5 mg/L, initially the N&P removal was seriously inhibited, but gradually recovered with the restored abundances of Nitrospira and PAOs. However, AOB, Nitrobacter and denitrifiers were found to be more vulnerable to high-concentration tetracycline with slow activity recovery. Consequently, this study offered useful information about long-term microbial responses to tetracycline in enhanced biological nutrient removal process.